2013
DOI: 10.1007/s10815-013-9983-3
|View full text |Cite
|
Sign up to set email alerts
|

Early compaction at day 3 may be a useful additional criterion for embryo transfer

Abstract: Thus, early compaction, sometimes observed at day 3, may serve as a useful additional criterion for selecting the embryos transferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The reduced proportion of high-quality embryos on day 3 could negatively influence the likelihood of progression to the blastocyst stage and, in turn, the likelihood of pregnancy and implantation (23). The decreased rate of compaction on day 3 in the dry culture could have resulted in a lower implantation rate and poorer overall clinical outcomes in this group because of the known correlation between compaction and implantation rates (24).…”
Section: Discussionmentioning
confidence: 99%
“…The reduced proportion of high-quality embryos on day 3 could negatively influence the likelihood of progression to the blastocyst stage and, in turn, the likelihood of pregnancy and implantation (23). The decreased rate of compaction on day 3 in the dry culture could have resulted in a lower implantation rate and poorer overall clinical outcomes in this group because of the known correlation between compaction and implantation rates (24).…”
Section: Discussionmentioning
confidence: 99%
“…Among the embryos that developed to more than 16 cell stages, morula is characterized by its appearance with unclear outlines of blastomeres following the process of compaction, and observed from day 3 or 4 after fertilization [42]. In fact, embryonic genome activation is known to generally occur in a part of morula stage, which causes embryos that undergo this phase to possibly proceed to compaction and cavitation [43]. Transcribed genes in this stage, engaged in metabolism of amino acids, carbohydrates, lipids, and proteins, regulate the system of energy metabolism in embryos, which is required for consequent development into BL [44].…”
Section: Discussionmentioning
confidence: 99%
“…Embryos that undergo compaction and cavitation become distinguishable and reflect embryo commitment to the next stage of development [ 56 ]. It has been reported that embryo quality on day 2 may be linked to the ability to undergo compaction on day 3 [ 57 ].…”
Section: Discussionmentioning
confidence: 99%